2022
DOI: 10.1155/2022/4931945
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Cardiothoracic Ratio as a Potential Marker of Left Ventricular Hypertrophy Assessed by Echocardiography

Abstract: The aim of the study was to verify the usefulness of the radiological cardiothoracic ratio as a potential marker of left ventricular hypertrophy assessed by echocardiography. The study included 96 patients (mean age: 49.52 ± 9.64 years). Chest radiograph in the PA projection and echocardiography were performed. In CR the measurement of the cardiothoracic ratio (CTR) was performed. Assuming CTR > 0.50, heart silhouette enlargement was diagnosed. In echocardiography, four types of left ventricular geometry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We also found that hypertension had an inverse association with mortality in patients with HF. Previous studies have shown that a baseline CTR > 0.5 in HF patients is associated with higher mortality and higher hospitalization rates [18,19]. Consistent with previous findings, our study found that CTR ≥ 0.62, which associated with cardiomegaly, is a powerful independent predictor of poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that hypertension had an inverse association with mortality in patients with HF. Previous studies have shown that a baseline CTR > 0.5 in HF patients is associated with higher mortality and higher hospitalization rates [18,19]. Consistent with previous findings, our study found that CTR ≥ 0.62, which associated with cardiomegaly, is a powerful independent predictor of poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…It may also predispose to stroke [2] . One of the main causes of death in Nigeria and other West African nations is cardiac disease [5] . Prompt diagnosis and treatment of heart disorders may be aided by early detection of cardiomegaly [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The normal range of CTR is between 0.42 and 0.50. Values that are more than 0.5 or less than 0.42 indicate pathologic situations like cardiomegaly [5] . Cardiothoracic ratio is affected by different factors such as age, gender, race, body posture and physique [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CHF generally have a higher CTR than healthy individuals [22], and a negative correlation between CTR and ejection fraction has been reported [23]. A higher CTR (>0.49) may be a marker of left ventricular hypertrophy (LVH), with a high accuracy of 84.4% [24]. Previous studies have reported that cardiomegaly, assessed by the CTR, is correlated with all-cause mortality and cardiovascular mortality [25,26].…”
Section: Introductionmentioning
confidence: 99%